Metagenomics next-generation sequencing for the diagnosis of central nervous system infection: A systematic review and meta-analysis - Qu, Chunrun; Chen, Yu; Ouyang, Yuzhen; Huang, Weicheng; Liu, Fangkun; Yan, Luzhe; Lu, Ruoyu; Zeng, Yu; Liu, Zhixiong (Frontiers in Neurology, 2022)
Abstract OBJECTIVE: Central nervous system (CNS) infection is a serious infectious disease accompanied by various complications. However, the accuracy of the current detection methods is insufficient for precision diagnosis leading to delayed treatment. The emerging metagenomic next-generation sequencing (mNGS) was increasingly adopted in the scope of clinical diagnostic laboratories. And our study evaluated the application of mNGS in the CNS infection diagnosis. METHODS: Following PRISMA 2022 guidelines, we searched relevant articles published in 7 databases including PubMed, Web of Science, Cochrane Library, which is published from January 2014 to January 2022. And high-quality articles related to mNGS applications in the CNS infection diagnosis were included. The comparison between mNGS and the gold standard of CNS infection such as culture, PCR or serology, and microscopy was conducted to obtain true positive (TP), true negative (TN), false positive (FP), and false negative (FN) values, which were extracted for sensitivity and specificity calculation. RESULTS: A total of 272 related studies were retrieved and selected strictly according to the including and excluding criteria. Meta-analysis results of the 12 included studies showed that the combined sensitivity was 77% (95% CI: 70% - 82%, I2=39.69%) and combined specificity was 96% (95% CI: 93% - 98%, I2=72.07%). Although the heterogeneity of our research is not strong, the sub-group analysis in the pathogen, region, age, and sample pre-treatment method was also conducted to ascertain potential confounders. The area under the curve (AUC) of the summary receiver operating characteristic curve (SROC) of mNGS for CNS infection was 0.91 (95% CI: 0.88-0.93). Besides, Deek’s Funnel Plot Asymmetry Test indicated no publication bias existed in including studies (Figure 3, p value>0.05). CONCLUSIONS: mNGS exhibited good sensitivity and specificity in the diagnosis of CNS infection and possessed excellent clinical application potential. However, the efficacy is still unstable requiring subsequent studies for its further clinical application improvement.